P242 Co-infections with cytomegalovirus (CMV) and sexually transmitted infections (STIs) in pregnant women. (14th July 2019) - Pinninti, Swetha; Pol, Barbara Van Der; Daniel, Grace; Fowler, Karen; Boppana, Suresh
Abstract : Background: Congenital cytomegalovirus infection (cCMV) is a leading cause of hearing loss and neurodevelopmental disabilities. An association between STIs and CMV including higher rates of CMV acquisition and reinfections in women with STIs has been shown in studies of selected populations of women attending STI clinics. However, the interaction between CMV and STIs in the genital tract and whether CMV and STI co-infection increases the risk of intrauterine transmission of CMV remains unclear. The objective of this study is to determine STI prevalence and CMV shedding rates in a cohort of unselected pregnant women. Methods: Vaginal swabs from a cohort of CMV seropositive women in labor from a multi-center study were analyzed. After DNA extraction from vaginal swabs, PCR was performed for detection of CMV, Neisseria gonorrhoeae (GC), Chlamydia trachomatis (CT) and Trichomonas vaginalis (TV). CMV genital shedding rates were compared between groups with and without STIs. Results: Approximately 11% (11/101)) of pregnant women in this cohort tested positive for STIs (10 with TV and 1 with TV and GC co-infection). None of the women with STIs were shedding CMV in the genital tract during labor compared to 24% (22/90) of women without STIs. No significant difference in racial distribution was noted between the groups with and without STIs (82% Black vs 58% Black respectively; p = 0.19). Among women shedding CMV in the genital tract, CMV viral load levels ranged from 1.2x102 IU/ml – 2.3x104 IU/ml. Conclusion: In a cohort of unselected pregnant women, none of the CMV seropositive pregnant women with STIs were shedding CMV in the genital tract. Our preliminary findings suggest CMV shedding is not associated with STIs detected late in pregnancy. A larger study is need to confirm these findings and to define the relationship between STIs and cCMV. Disclosure: No significant relationships.